Bridging the Gap: ESP Principles in Web Programming for Health Informatics Undergraduates - Kusumawati, Erna Adita; Sutrisno, Trismianto Asmo; Nisa’, Zakiyah Khoirun (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2026)
This study was aimed at identifying and analysing principles in effective ESP teaching in the context of web programming teaching and learning toward students in Applied Bachelor of Health Information Management Study Program of STIKes Mitra Husada Karanganyar. This study applied qualitative descriptive approach focussing on web programming teaching and learning through ESP. It utilized data from observations, interview, and document analysis to provide a straightforward and factual account of ESP principles. The result is English for Specific Purposes (ESP) teaching in web programming for students is conceptually and objectively aligned with the needs of the students. ESP teaching is fundamentally needs-driven, learner-centered, and highly contextualized to provide a deep understanding of the specific linguistic and communicative demands of the web development field, including technical vocabulary, specialized documentation genres, and collaborative communication skills. Methodologies such as genre-based learning, task-based learning, and Content and Language Integrated Learning (CLIL) are essential to integrate language and content, foster practical application, and ensure relevance to real-world industry practices.